An assessment of hand hygiene perception and practices among undergraduate nursing students in Lagos State: A pilot study - Afolabi Oyapero; Oyejoke Oyapero (Wolters Kluwer Medknow Publications, 2018)
BACKGROUND: The contaminated hands of health-care professionals (HCPs) is an implicated vector in the transmission of potentially pathogenic organisms to vulnerable patients. The aim of this study was to derive baseline data on hand hygiene (HH) practices among a cohort of students at the Lagos State School of Nursing and to determine their perception about the adequacy of instructions they receive. MATERIALS AND METHODS: A descriptive, cross-sectional study was conducted on a probability random sample of 69 nursing students at the Lagos State School of Nursing at the Alimosho Igando General Hospital. The knowledge, attitude, and practice as well as the perception of the respondents on the adequacy of their infection control instructions were obtained using an interviewer-administered questionnaire. Data entry and analysis were done using SPSS software version 20 (IBM Corp., Armonk, NY, USA), P < 0.05 was considered statistically significant. Multivariate linear and logistic regressions were done to assess which factors were truly significant predictors, with odds ratios (ORs) and 95% confidence intervals (CIs) specified as the measures of association between predictors and outcome variables. RESULTS: Majority of participants were ≤20 years old (50.7%, n = 35) and were in their second year of study (44.9%, n = 31). Participants were least knowledgeable about the importance of discarding gloves and not washing or reusing them (16 [23.1%]). The mean score on the Hand Hygiene Beliefs Scale was 86.2 ± 9.0, with scores ranging from 23 to 88 out of a possible high score of 115. The most positive health beliefs were associated with being a role model for HH (3.57 ± 0.52), while the worst was associated with imitating bad HH practices performed by senior colleagues (1.29 ± 1.20). Caring for a wound (60 [87.0%]) was most associated with the need for HH, while demonstration and clinical practice were rated as the most effective teaching methods. Results of the multivariate logistic regression analysis, with the outcome variable of good self-reported HH practices, revealed that the odds of appropriate behavior were higher if the student nurses were in their third year of study (OR = 1.59; 95% CI: 1.01-2.45). An appropriate behavior was also more likely in student nurses with a higher risk perception (OR = 1.54; 95% CI: 1.03-2.51). CONCLUSION: Despite the overwhelming evidence that HH is effective in the prevention of hospital-acquired infections, its performance among HCPs remains far less than optimal. Since students will someday be influencing future HH compliance behaviors of other health-care workers, the importance of HH should be adequately incorporated into their school curriculum.